Validation of race non-specific, adult plant leaf rust resistance genes Lr34 and Lr67 in some common wheat (Triticum aestivum L.) cultivars - Mishra, A.N.; Kaushal, K.; Dubey, V.G.; Shirsekar, G.S.; Prasad, S.V.Sai (The Indian Journal of Genetics and Plant Breeding, 2016)
Twelve common wheat cultivars with Lr34 postulated based on leaf tip necrosis and other observations were studied for adult plant resistance to leaf rust (Puccinia triticina) pathotype 77-5 (121R63-1), and validation of Lr34 and Lr67 through allelic tests. Line 897 and Frontana, known Lr34 carriers, served as checks. Resistance was governed by one dominant gene each in C 306, Kalyansona, Line 897, NI 5439 and WH 147; and by two dominant genes each in Frontana, GW 173, HD 2189, HI 1077, HP 1744, K 9107, PBW 175, PBW 373, and UP 2338. Allelic tests showed presence of Lr34 in Frontana, GW 173, HD 2189, HP 1744 and Line 897; and of Lr67 in C 306, NI 5439 and K 9107. Comparison is drawn with reports based on molecular markers. Our findings should be useful in multiple disease resistance breeding as Lr34 and Lr67 are associated with resistance to multiple wheat pathogens.